馬來西亞「後茅草行動」的華社變遷：以「動地吟」詩人群體為個案討論 - 曾維龍 (國立陽明交通大學出版社, 2018)
本文主要探討「後茅草行動」時期所出現的一批詩人群體，他們的形成以及實踐的困境。筆者以1987年至1998年之間「後茅草行動」時期為範疇，嘗試說明「後茅草行動」和馬華文學之間存在的聯繫。這一批詩人群體，主要由游川和傅承得號召聚集。通過參與「動地吟」現代詩朗誦的演出，他們積極以詩歌創作介入社會，反映當下。這一詩歌活動，橫跨越二十餘年的時間，幾乎每隔十年即呈現一系列的演出。按傅承得統計，在1987年至2012年之間在「動地吟」演繹的本土作品即有331篇，另有馬來文及巫譯作品6篇、國外作品23篇，共計360首詩。參與的詩人多達100人。這一現象產生了大量的創作文本，成為馬華文學研究的重要課題。本文闡述詩歌文本背後所可能存在的「支配／反支配」、「壓抑／反壓抑」、想像力等結構性問題，從側面反映「後茅草行動」時期馬來西亞華人社會族群本位的態度。

This paper discusses the emergence, formation, and practice of a group of poets that appeared during the ＂Post-Operasi Lalang＂ period. This article elaborates on the relationship between the ＂Post-Operasi Lalang＂ and the Ma-hua (Chinese Malaysian) literature in the period between 1987 and 1998. During this period, You Chuan (游川) and Poh Seng Titt (傅承得) have gathered a group of poets. By participating in the performances of ＂Dong Di Yin＂ (動地吟), they actively participated in the society through writing poetry that reflects the present. Spanning more than twenty years, this activity has presented series of performances almost every decade. According to Poh's statistics, there were 331 local works performed in the period from 1987 to 2012. Furthermore, there were 6 Malay works translated from Malay and 23 works from Western texts, reaching a total of 360 poems. There were more than 100 poets involved. This phenomenon has become an important topic in the study of Ma-hua literature. In a large amount of texts, the poets explored the structural problems such as ＂domination/anti-domination＂, ＂repression/ anti-repression＂ and imagination, particularly reflecting the Chinese society in Malaysia during the ＂Post-Operasi Lalang＂ period.
Keywords: 馬來西亞; 華人社會; 馬華文學; 茅草行動; 「動地吟」詩人; Malaysia; Chinese society; Malaysian Chinese literature; Operasi Lalang; Dong Di Yin